The American Yawp Vol. I To 1877 - Locke, Joseph L.; Wright, Ben (Open textbook library., 2019)
In an increasingly digital world in which pedagogical trends are de-emphasizing rote learning and professors are increasingly turning toward active-learning exercises, scholars are fleeing traditional textbooks. Yet for those that still yearn for the safe tether of a synthetic text, as either narrative backbone or occasional reference material, The American Yawp offers a free and online, collaboratively built, open American history textbook designed for college-level history courses. Unchecked by profit motives or business models, and free from for-profit educational organizations, The American Yawp is by scholars, for scholars. All contributors—experienced college-level instructors—volunteer their expertise to help democratize the American past for twenty-first century classrooms.